Gc-Ms And Ft-Ir Analysis For Determination Of Bioactive Compounds In Fenugreek (Trigonella Foenum-Graecum L.) Var. ‘gm-2’ (Applied Biological Research, 2017)
The present study focused on the classification and identification of bioactive  components, along with functional groups, present in methanolic seed-extract  of fenugreek (Trigonella foenum-grecum L.) var. Gujarat Methi-2 (GM-2).  Seed were analyzed using GC-MS-QP2010 Ultra and FT-IR by alpha ECO ATR spectrometer. The mass spectra of compounds matched with National  Institute of Standards and Technology (NIST) library. GC/MS analysis of  methanol extract of var. GM-2 seed revealed the presence of 50 bioactive  compounds amongst which 9, 12-octadecadienoic acid (Z, Z)- (32%), mome  inositol (12%), cyclopentanol (9%) and 2-methylpyrrolidine (3%) were most  dominant. Peaks obtained from FT-IR indicated the presence of various  functional groups. The results offer a platform for using var. GM-2 seed as  herbal alternative for synthetic antimicrobial and antioxidants sources.
Keywords: FT-IR spectroscopy; Gujarat Methi-2; GC-MS analysis; medicinal properties; Trigonella foenum-graecum